Comment on ‘Criterion placement threatens the construct validity of neural measures of consciousness’ - Kristian Sandberg; Morten Overgaard (eLife)
In a recent article Fahrenfort and colleagues demonstrate that auditory and monetary punishment change the criteria that participants use to rate the clarity of perception (Fahrenfort et al., 2025). This leads them to conclude that “subjective measures do not reliably measure the construct they intend to measure” and that their construct validity is threatened. Here, we argue that the main findings had already been demonstrated in other experiments, and the general limitations of subjective measures has been known for decades without the field dismissing their usefulness. We further argue that the experimental manipulations of Fahrenfort and colleagues are so radical that they could be used to invalidate essentially any psychological/cognitive test. In our view, both of the above-mentioned conclusions are thus inappropriate considering the evidence presented, and we believe that the take-home message both before and after the study of Fahrenfort and colleagues is to acknowledge the limitations of subjective reports when they are used.